Lung cancer screening: not all nodules are created equal - Shukla, Gaurav; Williams, Noelle L.; Luminais, Christopher; Lu, Bo; Shi, Wenyin (Journal of Thoracic Disease, 2016)
The incidence and mortality from bronchogenic malignancies continue to be high, with an estimated 224,000 new cases and an estimated 158,000 deaths in the United States in 2016 (1). Approximately 75% of patients present with locally advanced disease or metastatic disease, usually beyond the scope of curative therapies (2). This has prompted the development of screening programs which utilize low-dose chest computed tomography (CT) imaging in asymptomatic high-risk individuals. The NELSON trial is a Dutch/Belgian screening trial randomizing high-risk patients (as determined by smoking history and age) to receive either no screening or a series of low-dose chest CT imaging studies at prespecified time-points (year 1, 2, 4, and 6). Patients with suspicious nodules found on the screening CT imaging were subsequently evaluated with repeat imaging, biopsy, or other appropriate interventions (3). Over 15,000 patients have been accrued; the investigators hypothesized that screening will decrease 10-year lung cancer mortality by at least 25% (3). While the primary outcome data continue to mature, the available information on over 7,500 patients with serial CT imaging lends itself to preliminary analysis.